Handbook of research on new media literacy at the K-12 level [ issues and challenges - Subramaniam, R. [ (Ramanathan)] , 1952-; Tan, Leo Wee Hin , 1944- (Information Science Reference, 2009)
"This book provides coverage of significant issues and theories currently combining the studies of technology and literacy"--Provided by publisher.